Nowcasting private consumption with TV sentiment - Matthias W. Uhl (ETH Zurich, KOF Swiss Economic Institute, 2011)
We perform principal components analyses of the University of Michigan Index of Consumer Sentiment and TV sentiment in order to gain information on their structure and information content. By introducing the new sentiment variable TV sentiment, gathered from sentiment from statements from over 10,000 TV news broadcasts in the United States, we find that TV sentiment adds great value in nowcasting private consumption. We further find that TV sentiment performs markedly better than the Index of Consumer Sentiment, suggesting that using sentiment from TV news has more explanatory power than survey-based sentiment.
Keywords: D12; E21; 330; TV sentiment; consumer sentiment; private consumption; Medienverhalten; Fernsehen; Konsumentenverhalten; Michigan